2023
DOI: 10.1200/op.22.00458
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Among Young Adult Survivors of Childhood Cancer With Cognitive Impairment: An Analysis of the Project Forward Cohort

Abstract: PURPOSE: Young adult childhood cancer survivors (YACCSs) are often impacted by cancer-related cognitive impairment (CRCI) and psychological distress. Using the Project Forward Cohort, we evaluated the relationship between CRCI and substance use behaviors. METHODS: YACCSs were surveyed between 2015 and 2018 (N = 1,106, female = 50.8%, Hispanic = 51.5%, median age = 25.5 years). Associations between CRCI and substance use (tobacco, binge drinking, marijuana, prescription drug misuse, and e-cigarette/vaporizer) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…studied substance misuse among young adult childhood cancer survivors (median age: 26.5y). They found that, among these survivors, substance misuse behavior proportion was 34% for binge drinking, 11% for cigarette use, and 7% for e-cigarette/vaporizer use [ 12 ]. Cappelli et al .…”
Section: Introductionmentioning
confidence: 99%
“…studied substance misuse among young adult childhood cancer survivors (median age: 26.5y). They found that, among these survivors, substance misuse behavior proportion was 34% for binge drinking, 11% for cigarette use, and 7% for e-cigarette/vaporizer use [ 12 ]. Cappelli et al .…”
Section: Introductionmentioning
confidence: 99%